Predictors of In-hospital Mortality Among Patients Presenting with Variceal Gastrointestinal Bleeding - Amith S Kumar (The Saudi Journal of Gastroenterology, 2015)
Background/Aim: The recent years have witnessed an increase in number of people harboring chronic liver diseases. Gastroesophageal variceal bleeding occurs in 30% of patients with cirrhosis, and accounts for 80%-90% of bleeding episodes. We aimed to assess the in-hospital mortality rate among subjects presenting with variceal gastrointestinal bleeding and (2) to investigate the predictors of mortality rate among subjects presenting with variceal gastrointestinal bleeding. Patients and Methods: This retrospective study was conducted from treatment records of 317 subjects who presented with variceal upper gastrointestinal bleeding to Government Medical College, Patiala, between June 1, 2010, and May 30, 2014. The data thus obtained was compiled using a preset proforma, and the details analyzed using SPSSv20. Results: Cirrhosis accounted for 308 (97.16%) subjects with bleeding varices, with extrahepatic portal vein obstruction 9 (2.84%) completing the tally. Sixty-three (19.87%) subjects succumbed to death during hospital stay. Linear logistic regression revealed independent predictors for in-hospital mortality, including higher age (P = 0.000), Child-Pugh Class (P = 0.002), altered sensorium (P = 0.037), rebleeding within 24 h of admission (P = 0.000), low hemoglobin level (P = 0.023), and serum bilirubin (P = 0.002). Conclusion: Higher age, low hemoglobin, higher Child-Pugh Class, rebleeding within 24 h of admission, higher serum bilirubin, and lower systolic blood pressure are the independent predictors of in-hospital mortality among subjects presenting with variceal gastrointestinal bleeding.